The Worthing saga - Card, Orson Scott; Copyright Paperback Collection (Library of Congress) (New York : Tom Doherty Associates Book, 1990)
It was a miracle of science that permitted human beings to live, if not forever, then for a long, long time. Some people, anyway. The rich, the powerful--they lived their lives at the rate of one year every ten. Somec created two societies: that of people who lived out their normal span and died, and those who slept away the decades, skipping over the intervening years and events. It allowed great plans to be put in motion. It allowed interstellar Empires to be built. It came near to destroying humanity. After a long, long time of decadence and stagnation, a few seed ships were sent out to save our species. They carried human embryos and supplies, and teaching robots, and one man. The Worthing Saga is the story of one of these men, Jason Worthing, and the world he found for the seed he carried.
This book brings together all the Worthing stories for the first time in one volume.
Keywords: Space colonies -- Fiction; Life on other planets -- Fiction; Science fiction; Science fiction